La dimension internationale de la recherche en sciences de l'éducation et de la formation : normes académiques, spécificités et paradoxes - Brigitte Albero; Angela Barthes
A low response rate to European programs and a short English-language bibliometric literature make French education and training sciences (ETS) regarded as little invested in international relationships. However, the creation of a database of researchers and doctoral students during the period of 2014-2018 contradicts this interpretation. Why such distortion? The quantitative study of the base makes it possible to formulate two observations: 1) an important commitment of the teams in multidisciplinary and multicultural approaches answering the requirement of the international institutions and the contemporary stakes in the matter; 2) the absence of support and promotion of national institutions stems from a conception of science activity measurement which does not match the practices of scientific discipline. Scientific and academic, but also socio-political and professional, standpoints differ in the two analyzes; which leads to questioning the relationship that scientific discipline maintains with the international standardization of evaluation. This article questions the hierarchy of disciplines, cultures and forms of research for the benefit of international cooperation in the 21st century with a view to human development.